2015
DOI: 10.3390/ijms160510337
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Melatonin on the Extracellular-Regulated Kinase Signal Pathway Activation and Human Osteoblastic Cell Line hFOB 1.19 Proliferation

Abstract: It has been shown that melatonin may affect bone metabolism. However, it is controversial whether melatonin could promote osteoblast proliferation, and the precise molecular mechanism of melatonin on osteoblast proliferation is still obscure. In this study, the results of the CCK-8 assay showed that melatonin significantly promoted human osteoblastic cell line hFOB 1.19 cell proliferation at 1, 2.5, 5, 10, 25, 50 and 100 µM concentrations for 24 h, but there were no significant differences among the groups. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 56 publications
3
8
0
Order By: Relevance
“…It mainly depends on the following mechanisms based on the G-protein-coupled receptor (MT2): enhancing osteoblast activity, inhibiting osteoclast differentiation and scavenging oxygen free radicals. We also found that melatonin promotes osteoblast proliferation in a concentration-dependent manner (Liu et al, 2011;Liu et al, 2012;Xiong et al, 2015;Tao and Zhu, 2018). Notably, melatonin significantly induces osteoblast differentiation and matrix mineralization, but the underlying mechanism remains unclear (Roth et al, 1999;Park et al, 2011;Maria et al, 2018).…”
Section: Introductionsupporting
confidence: 56%
“…It mainly depends on the following mechanisms based on the G-protein-coupled receptor (MT2): enhancing osteoblast activity, inhibiting osteoclast differentiation and scavenging oxygen free radicals. We also found that melatonin promotes osteoblast proliferation in a concentration-dependent manner (Liu et al, 2011;Liu et al, 2012;Xiong et al, 2015;Tao and Zhu, 2018). Notably, melatonin significantly induces osteoblast differentiation and matrix mineralization, but the underlying mechanism remains unclear (Roth et al, 1999;Park et al, 2011;Maria et al, 2018).…”
Section: Introductionsupporting
confidence: 56%
“…However, some studies have noted that melatonin has a negative effect on bone [32]. Based on the existing literature, we chose four melatonin concentrations that respectively have had positive and negative effects in vivo and in vitro:100 mg/kg and 50 mg/kg melatonin for in vivo tests and 10μM and 1 mM melatonin for in vitro tests [7, 8, 33, 34]. Our experiments demonstrated for the first time that melatonin suppresses osteoporosis in diabetes mellitus.…”
Section: Discussionmentioning
confidence: 99%
“…Melatonin inhibits fatty acid-induced triglyceride accumulation in ROS17/2.8 cells, which may promote osteoblast differentiation and inhibit bone loss. 80 Moreover, melatonin enhances osteoblastic differentiation in vitro [81][82][83][84][85][86][87][88] and promotes mouse cortical bone formation in vivo. 81…”
Section: Melatonin Promotes Osteogenesis In Osteoblastsmentioning
confidence: 99%